HOUSE BUYER'S ACCEPTANCE TO THE GREEN HOME CONCEPT - Yusoff, Mohd Nazaruddin; Talib, Azlizan; binti Abdul Karim, Siti Maisarah (Journal of Islam and Science, 2015)
Being more knowledgeable about the negative impacts of massive exploitation and misuse of land and natural resources, and how they potentially endanger their life and home, today's housing consumers has become more conscious of nature and concerned with damages happening to it. The immense construction of conventional house which is aimed at fulfilling people's demand on residence in Malaysia is claimed to inevitably result in chronical damage to environment for it employs high number of labours and produces large amount of carbon dioxide into the air. Therefore, the Green Home concept is introduced to sort out the problems without reducing energy, air quality, space and natural recourse. Nevertheless, the concept itself is still new for people in Malaysia and will take time and effort to understand and accept. This study is to reveal the level of people's understanding of this Green Home concept as well as its primary components and implementation procedures in Malaysian housing industry.